Using biological traits to get insights into the bentho-demersal community sensitivity to trawling in the Celtic Sea. (7th February 2021) - Dupaix, Amaël; Mérillet, Laurène; Kopp, Dorothée; Mouchet, Maud; Robert, Marianne
Abstract: Coastal marine ecosystems are under many pressures, including bottom trawling, which is the most widespread human activity that directly affects seabed habitats. Therefore, it is of great importance to characterize the impacts of bottom trawling on bentho-demersal communities, which can be done through the study of indicators sensitive to trawling pressure. Using a functional indicator applied to 54 underwater video transects, we mapped the sensitivity to trawling of epibenthic invertebrates and fish communities in the Celtic Sea. We determined the relative influence of environmental and fishing variables on sensitivity and traits distribution. Our results suggest that community sensitivity to trawling is mainly driven by a spatial gradient of depth and primary productivity that separates the area into two main regions: a shallow, productive area, with low sensitivity and a higher abundance of swimming and crawling organisms, and a deeper, less productive area, with higher sensitivity due to a higher abundance of fixed, filter-feeding organisms. Fishing intensity also drives the sensitivity of communities confirming that they have already been shaped by a long history of mixed fisheries. The methodology used here provides a valuable monitoring tool and could be used to predict communities' response to changes in fishing intensity and climate change.